Study of the decays D-s(+) -> (KSK+)-K-0 and (KLK+)-K-0 - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2019)
Using an e(+)e(-) annihilation data sample corresponding to an integrated luminosity of 3.19 fb(-1) and collected at a center-of-mass energy root s = 4.178 GeV with the BESIII detector, we measure the absolute branching fractions B(D-s(+) -> (KSK+)-K-0) = (1.425 +/- 0.038(stat). +/- 0.031(syst).)% and B(D-s(+) -> (KLK+)-K-0) = (1.485 +/- 0.039(stat). +/- 0.046(syst).)%. The branching fraction of D-s(+) -> (KSK+)-K-0 is compatible with the world average and that of D-s(+) -> (KLK+)-K-0 is measured for the first time. We present the first measurement of the K-S(0)-K-L(0) asymmetry in the decays D-s(+) -> (KS,LK+)-K-0, and R((Ds+KS,LK+)-K-0) = B(D-s(+) -> (KSK+)-K-0)-B(D-s(+) -> (KLK+)-K-0)/B(D-s(+) -> (KSK+)-K-0)+B(D-s(+) -> (KLK+)-K-0) = (-2.1 +/- 1.9(stat). +/- 1.6(syst).)%. In addition, we measure the direct CP asymmetries A(CP) (D-s(+/-) -> (KSK +/-)-K-0). (0.6 +/- 2.8(stat). +/- 0.6(syst).)% and A(CP)(D-s(+/-) -> (KLK +/-)-K-0 ) = (-1.1 +/- 2.6(stat). +/- 0.6(syst))%.